Pengaruh Efikasi Diri dan Ekspektasi Pendapatan, Terhadap Minat Berwirausaha Siswa SMK (SMK Al-Madina) - Ilmaniati, Anita; Musihudin, Muslihudin (Jurnal Media Teknik dan Sistem Industri, 2017)
Cianjur regency is an area that has the potential to develop the regional economy through creative industries-based entrepreneurship. Cianjur is supported by many vocational schools (SMK) with relevant expertise fields to develop regional potential through entrepreneurship. Based on this, it is very important to develop entrepreneurship interest in SMK students in Cianjur by identifying factors that influence student entrepreneur interest. Factors of entrepreneur interest identified in this research are self efficacy and income expectation. The purpose of this research is to analyze the effect of self efficacy and income expectation on student entrepreneurship interest of SMK (Al-Madina, Cianjur). This research was conducted by distributing questionnaires to students of SMK Al-Madina Cianjur and using PLS-SEM model in testing. The results showed that the relationship of self efficacy variable to entrepreneurship interest was significant with T-statistics of 2,996 (> 1,96), and the relationship of income expectation variable to entrepreneur interest was significant with T-statistic 4,121 (> 1,96). R-Square value of this research model is 0.228 which shows that there are still other variables that will explain student entrepreneur interest in Cianjur.Keywords: Self efficacy; income expectations; entrepreneurial interest; PLS-SEMÂ Â